Towards the validation of endogenous steroid testing in wildlife hair. Issue 3 (15th December 2018) - Koren, Lee; Bryan, Heather; Matas, Devorah; Tinman, Simon; Fahlman, Åsa; Whiteside, Douglas; Smits, Judit; Wynne‐Edwards, Katherine
Abstract: Hair analysis is emerging as a popular tool to examine stress and reproduction hormone levels in wild mammals. The reliability of this approach, however, depends on an understanding of steroid hormone incorporation into hair as well as appropriate validations. We reviewed studies that have examined steroid hormones in wildlife hair with the goal of summarizing the analytical, physiological, and biological evidence that this approach is meaningful. Accordingly, we differentiated among validations aimed at evaluating the reliability of the analytical method versus those designed to assess whether hormone levels in hair reflect physiologically meaningful processes in the target species. Our literature survey revealed that endogenous steroids have been examined in hair from 40 species of nonhuman animals across seven mammalian classes. Although the majority (85%) of 72 studies reported analytical validations of the method, physiological validations have only been reported for five species. Moreover, results of physiological validations were inconsistent among studies. This highlights the need for further research, carefully designed to differentiate between the multiple purported models of steroid incorporation into hair in species with different types of hair and different hair growth patterns. To complement our review of published studies, we present new data supporting a positive relationship between levels of the steroid, cortisol, in hair and blood across eight mammalian species. In addition, we present novel results from a laboratory‐based study showing variable hair growth in genetically identical laboratory mice that were kept under controlled conditions. Synthesis and applications . Collectively, this Review reveals substantial progress towards the validation of stress hormone assays in hair from a variety of wildlife species. Further validations of reproductive steroids, combined with appropriate physiological validations, would expand the potential applications of hair analyses in wildlife research. As a key example, physiological data can provide mechanistic insights into species' responses to change and may therefore contribute to conservation planning. Abstract : Collectively, this Review reveals substantial progress towards the validation of stress hormone assays in hair from a variety of wildlife species. Further validations of reproductive steroids, combined with appropriate physiological validations, would expand the potential applications of hair analyses in wildlife research. As a key example, physiological data can provide mechanistic insights into species' responses to change and may therefore contribute to conservation planning.